Elemental and structural changes in illite/smectite mixed-layer clay minerals during diagenesis in Kimmeridgian- Volgian (- R yazanian) clays in the Central Trough, North Sea and the Norwegian Danish Basin - Lindgreen, Holger (Bulletin of the Geological Society of Denmark, 1991)
The literature on the diagenetic conversion of smectite layers to illite layers in mixed-layer illite/smectite is reviewed. According to this smectite layers are converted to illite layers during diagenesis at temperatures above 55°C and illite/smectites become IS ordered at about 100°C and at illite percentages of about 80%. Charge and elemental composition seem, beside temperature, to be of importance in the process. Investigations from metamorphic and hydrothermal areas have also found a conversion of smectite to illite layers with increasing temperature. In hydrothermal experiments, the process has been found to occur at temperatures of 250°C and above. Investigations from metamorphic areas have shown that the increase in amount of illite layers in _illite/smectite during short lived heating events is very slow compared to the increase in vitrinite reflectancy. The elemental changes during illite layer formation are a substitution of AIH for Si4+ in the tetrahedral sheet and a fixation of K• between 2: 1 units. Some investigations have also found substitution of AlH for Mg2+ and Fe and a reduction of FeH in the octahedral sheet. The changes seen during the hydrothermal experiments and in hydrothermal areas are different from the diagenetic changes in that higher negative charges are created and Na+ and Ca2+ are fixed under hydrothermal conditions. Two models have been proposed for the diagenetic formation of illite layers from smectite layers: 1) A solid-state AlH for Si4+ substitution in the tetrahedral sheets of smectite layers and subsequent fixation of K+ and interlayer collapse, giving illite layers; and 2) A dissolution of smectite layers and crystallization and growth of illite crystals. K+ supply is the main control on the formation of illite layers from smectite. Even in systems with sufficient K+ available, other cations such as Mg>+, Ca2+, and Na+ may inhibit K•- fixation and illite layer formation. The release of clay transformation water and its possible role in petroleum migration has been the subject of several investigations. There seems in most cases to be a coincidence between collapse of interlayer space (assumed to release interlayer water) and the generation of petroleum. But the role of the water released during clay diagenesis is not clear. The geology of the Central Trough and the Norwegian-Danish Basin is shortly reviewed. The source of the Upper Jurassic clays was probably mainly the Fennoscandian Shield. In addition volcanic material including ash has probably been sedimented in the North Sea region during Upper Jurassic. Cores and hand-picked cuttings samples from the Manda!, Farsund and Haugesund Formations in the Central Trough and from the Sauda, Tau, B0rglum and Bream Formations in the Norwegian-Danish Basin have been investigated. Intact bulk rock samples were ion-milled and investigated by high resolution transmission electron microscopy (HRTEM). The samples were also ultrasonically and chemically treated and the mixed-layer illite/smectite isolated by centrifuging. The illite/smectite samples thus obtained were investigated by HRTEM, by transmission electron microscopy (TEM) ort shadowed specimens, by X-Ray diffraction (XRD), by 27AI and 29Si magic angle spinning, nuclear-'magnetic resonance spectroscopy (mas-nmr), by infrared spectroscopy (IR), and by chemical al):\lysi_s for elements and NH,+. lllite percentages and ordering in illite/smectite were estimated by computer simulation of XRD patterns by the NEWMOD program for two-component systems and by a program for three component systems. The interpretations of the HRTEM images of illite/smectite structures in intact bulk rock were supported by computer simulations. The results of XRD on coarse clay fractions indicated that the main source area for the Upper Jurassic claystones was the Fennoscandian Shield. XRD supported by computer simulations showed that the amount of illite layers in illite/smectite was between 40% and 80% illite layers in randomly ordered or I-S segregated illite/smectite, between 80% and 90% in mainly IS ordered illite/smectite, and about 95% illite layers in ISII ordered illite/smectite. 10--14 A distances were seen in lattice fringes by HRTEM on intact bulk rock and are probably due to smectite layers with non-contracted interlayer space, whereas 10 A lattice fringes can be due to illite or collapsed smectite and 14 A distances to chlorite_ or non-collapsed smectite. 10 A lattice fringes with periodically enhanced contrast were observed by HRTEM on intact bulk rock in all Central Trough samples investigated. Regular 20 A period sequences of such enhanced contrast were most frequent but also 30 A period sequences and sequences with enhanced contrast occurring randomly along c* were seen. These particles are MacEwan illite/smectite particles. The specimens prepared for HRTEM from dispersed illite/smectite contained a large amount of thin particles with 10 A period in contrast but also, in IS ordered illite/smectite, a large number of particles with 20 A periodically enhanced contrast, MacEwan particles. It is concluded that the thin particles seen by HRTEM and TEM on specimens prepared from dispersed illite/smectite have probably formed by dispersion of the thick particles seen by HRTEM in intact bulk rock. The illite/smectite from the Norwegian-Danish Basin, with 65--75% illite layers and randomly ordered or 1-S segregated, is probably detrital. Similar illite/smectite at shallow depth (less than about 3 km) and low temperatures (less than about l00°C) in the Central Trough is probably also detrital, but at larger depths and higher temperatures it is diagenetically changed to predominantly IS ordered illite/smectite with 80--95% illite layers. This change occurs at a vitrlnite reflectancy of about 0.65%, i.e. at about oil generation. Chemical analysis and mas-nmr showed that the formation of illite layers is accompanied by an increase in tetrahedral Al arid a minor increase in octahedral Al, by a decrease in tetrahedral Si and by a minor decrease in octahedral Mg and Fe. Analysis of pore water from Upper Jurassic claystone cores gave ratios for K+/NH4 + in pore water similar to those in illite/smectite from the same depth, indicating that the relative amounts of K+ and NH/ control the fixation of these cations in illite/smectite. The ordering of illite and smectite layers in MacEwan particles in intact bulk rock, observed in images as 20 A (and sometimes 30 A) periods of enhanced contrast, can only have formed during solid-state smectite to illite formation, the polarization effect probably being responsible. The chemical analyses show that the illite layers have charges of about -0.8, less than the ideal -1.0 of mica. Such low charge illite layers can form during a solid-state transformation. It is concluded that the formation of illite layers from smectite layers in the Upper Jurassic claystones is a solid-state transformation.